The Effect of Interface Modifications Combination of Multiple Friction Blocks on Truck Brake Squeal. Issue 1 (22nd December 2021) - Wu, Y. K.; Lu, C.; Yin, J. B.; Micheale, Y. G.; Wang, Q.; Wang, X. C.
Abstract: In order to study the effect of interface modifications combination of multiple friction blocks on truck brake squeal, a field test was carried out in this study. In the test, the vibration acceleration and the noise signals of the truck braking system were collected. The test results showed that the high-frequency squeal noise during braking resulted from the frictional vibration of the braking system. A simplified finite element model of the heavy truck braking system was established to investigate the effect of slotting and chamfering of friction block on brake squeal. The results of complex eigenvalue analysis indicate that the interface modifications have a great influence on truck brake squeal. A proper combination of slotting and chamfering of friction blocks is useful for the reduction of brake squeal tendency. This study can provide guidance for the design and optimization of silent braking system.